Frequency of Extra-Intestinal Manifestations of Ulcerative Colitis in Patients Presenting in A Tertiary Care Hospital - Hussain, Maria; Rashid, Saqib; Butt, Ramza Naeem; Yousaf, Haroon; Javed, Haroon; Ijaz, Shanza (Biological and Clinical Sciences Research Journal, 2025)
Ulcerative Colitis (UC) is a chronic inflammatory bowel disease primarily affecting the colon and rectum. However, a significant proportion of patients also experience extra-intestinal manifestations (EIMs), which may involve the musculoskeletal, dermatological, ocular, and hepatobiliary systems. These manifestations can complicate the clinical course and significantly impact the patient's quality of life. Objective: To determine the frequency and distribution of extra-intestinal manifestations in patients with UC presenting at a tertiary care hospital and assess associations with demographic and clinical factors. Methods: This cross-sectional study was conducted over three months from January to March 2025, at the Department of Medicine, Shalamar Hospital, Lahore. A total of 125 patients with a confirmed diagnosis of UC were enrolled using non-probability consecutive sampling. Data were collected through a structured proforma, with confirmation of EIMs by relevant specialists. Statistical analysis was performed using SPSS version 23. Chi-square and t-tests were applied to assess associations, with a p-value < 0.05 considered significant. Results: Out of 125 patients, 47 (37.6%) exhibited extra-intestinal manifestations. Musculoskeletal involvement was the most common (25.6%), followed by dermatological (12.0%), hepatobiliary (11.2%), and ocular (10.4%) manifestations. A statistically significant association was observed between longer disease duration and the presence of EIMs (mean duration: 8.2 ± 2.4 years vs. 5.6 ± 2.1 years, p = 0.0004). No significant gender difference was found, although musculoskeletal symptoms were more common in males and dermatological conditions were more frequent in females. Conclusion: EIMs are a common and clinically significant aspect of UC, affecting over one-third of patients in this study. The findings highlight the importance of early recognition and multidisciplinary management of EIMs, particularly in patients with longer disease duration. Routine screening and inter-specialty coordination can facilitate timely diagnosis and enhance patient outcomes. Further multicenter longitudinal studies are warranted to explore the long-term impact and progression of EIMs in diverse populations.